Mid-regional proatrial natriuretic peptide for predicting prognosis in hypertrophic cardiomyopathy. Issue 3 (26th July 2019) - Bégué, Céline; Mörner, Stellan; Brito, Dulce; Hengstenberg, Christian; Cleland, John G F; Arbustini, Eloisa; Galve, Enrique; Wichter, Thomas; Richter, Anette; Golmard, Jean-Louis; Bernard, Maguy; Dubourg, Olivier; et al.
Abstract : Objectives: N-terminal probrain natriuretic peptide (NT-proBNP) predicts mortality and the development of heart failure in hypertrophic cardiomyopathy (HCM). Mid-regional proatrial natriuretic peptide (MR-proANP) is a stable by-product of production of atrial natriuretic peptide. We sought to compare the prognostic value of MR-proANP and NT-proBNP in HCM. Methods: We prospectively enrolled a cohort of patients with HCM from different European centres and followed them. All patients had clinical, ECG and echocardiographic evaluation and measurement of MR-proANP and NT-proBNP at inclusion. Results: Of 357 patients enrolled, the median age was 52 (IQR: 36–65) years. MR-proANP and NT-proBNP were both independently associated with age, weight, New York Heart Association (NYHA) class, left ventricular ejection fraction (LVEF), wall thickness and left atrial dimension. During a median follow-up of 23 months, 32 patients had a primary end point defined as death (n=6), heart transplantation (n=8), left ventricular assist device implantation (n=1) or heart failure hospitalisation (n=17). Both NT-proBNP and MR-proANP (p<10 –4 ) were strongly associated with the primary endpoint, and the areas under the receiver operating characteristic (ROC) curves for both peptides were not significantly different. However, in a multiple stepwise regression analysis, the best model for predicting outcome was NYHA 1–2 vs 3–4 (HR=0.35, 95% CI 0.16 to 0.77, p<0.01), LVEF (HR=0.96, 95% CI 0.94 to 0.98, p=0.0005) and MR-proANP (HR=3.77, 95% CI 2.01 to 7.08, p<0.0001). Conclusions: MR-proANP emerges as a valuable biomarker for the prediction of death and heart failure related events in patients with HCM.